Unity in Diversity: the Interaction of Literature and Art of the Major Religious and Cultural Systems of India - O. G. Ultsiferov (Vestnik MGIMO-Universiteta)
The article examines one of the main questions of intercommunications between main religious and cultural systems in India: Hinduism, Buddhism, Islam and Christianity in literature and art. The article, using the actual material, focuses the similarities and differences between those systems, results the basic data on the interaction of these systems in literature and art and shows the mutual influence and interaction of such different systems.